MARAKKA’ BOLA TRADITION AMONG THE BUGIS COMMUNITY OF BARRU: A CULTURAL EXPRESSION OF SOLIDARITY, LOCAL WISDOM, AND ISLAMIC VALUES - Mubarak, Ahmad Yusuf; Khaerussalam , Ahmad; Mubarak, Ahmad Zaky; Sukmawardani, Andi Lili; Baharuddin, Baharuddin; Abrar, Muhammad Yadri (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
The Marakka’ Bola tradition is an intangible cultural heritage of the Bugis people in Barru Regency that reflects local wisdom through the collective relocation of traditional stilt houses. Amidst the challenges of modernization that threaten to erode communal values, a comprehensive understanding of the function of this tradition is very important. This study aims to provide a descriptive analysis of the procedural aspects, cultural values, social symbolism, and Islamic perspectives contained in the Marakka’ Bola tradition. A descriptive qualitative method was used, with data collected through a review of scientific articles, visual documentation, and media reports. The data was then analyzed thematically to interpret the cultural, social, and religious dimensions of the tradition. The findings of the study show that Marakka’ Bola not only embodies social solidarity and the preservation of ancestral heritage, but is also in line with Islamic principles, namely ta’awun (mutual assistance) and ukhuwah (brotherhood). This tradition continues to function as a unifying force and a dynamic tool for the intergenerational transmission of social values and character.